Challenge levels of everyday technologies as perceived over five years by older adults with mild cognitive impairment. (4th April 2018) - Hedman, Annicka; Kottorp, Anders; Almkvist, Ove; Nygård, Louise
ABSTRACT: Background: In clinical practice, efficient and valid functional markers are needed to detect subtle cognitive and functional decline in mild cognitive impairment (MCI). This prospective study explored whether changes in perceived challenge of certain everyday technologies (ETs) can be used to detect signs of functional change in MCI. Methods: Baseline and five-year data from 37 older adults (mean age 67.5 years) with MCI regarding their perceived ability to use ET were used to generate Rasch-based ET item measures reflecting the relative challenge of 46 ETs. Actual differential item functioning in relation to time was analyzed based on these item measures. Data collection took place in 2008–2014. Results: Seven (15%) of the ETs included were perceived to be significantly more challenging to use at year five compared to at baseline, while 39 ETs (85%) were perceived to be equally challenging to use, despite the fact that the participants' perceived ability to use ET had decreased. Common characteristics among the ETs that became more challenging to use could not be identified. The dropout rate was 43%, which limits the power of the study. Conclusions: Changes in the perceived challenge of ETs seem to capture functional change in persons with cognitive decline. Both easier and more challenging ETs typically used at home and in society need to be addressed to capture this functional change because significant changes occurred among ETs of all challenge levels and within all types of ETs.